2006
DOI: 10.1097/01.bpo.0000187998.91837.b2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Recurrent Anterior Sternoclavicular Joint Instability

Abstract: Chronic anterior sternoclavicular joint (SCJ) instability may cause pain and persistent functional limitation in active patients. Although SCJ reconstruction and medial clavicular resection have been advocated in these situations, the results of surgical treatment are not well characterized. The purpose of this investigation was to determine the functional outcome of surgical treatment in adolescent and young adult patients with chronic recurrent anterior SCJ instability. Fifteen patients with chronic recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 17 publications
0
96
0
2
Order By: Relevance
“…One patient had postoperative shoulder impairment (14%). Bae et al [4] treated nine chronic anterior luxations in children using tendon grafts, resulting in an average postoperative SST score of 11.4. These results are difficult to compare with our results because Bae et al [4] operated on children and Armstrong and Dias [3] did not use comparable outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One patient had postoperative shoulder impairment (14%). Bae et al [4] treated nine chronic anterior luxations in children using tendon grafts, resulting in an average postoperative SST score of 11.4. These results are difficult to compare with our results because Bae et al [4] operated on children and Armstrong and Dias [3] did not use comparable outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Bae et al [4] treated nine chronic anterior luxations in children using tendon grafts, resulting in an average postoperative SST score of 11.4. These results are difficult to compare with our results because Bae et al [4] operated on children and Armstrong and Dias [3] did not use comparable outcome measures. Glass et al [12] and Abbidin et al [1] reported Constant-Murley scores and had lower functional scores than we found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors correctly emphasize the risks with this technique, but mediastinal complications have not been reported in experienced hands. Bae et al [1] reported nine successful cases, with simple shoulder test scores averaging 11.2 and no complications, failures, or reoperations. These results mirror my clinical experience with 15 similar cases using this approach.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…However, some patients may develop chronic anterior instability and may continue to present symptoms. In these cases, surgical treatment is indicated (27). Sternoclavicular dislocations usually occur following traumatic events.…”
Section: Sternoclavicular Dislocationmentioning
confidence: 99%